2017
DOI: 10.5152/npa.2017.12711
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Model of Depression Based on Interpersonal Relationships: The Mediating Role of Coping Strategies and Loneliness

Abstract: Depression is a multifactorial disorder with various causes such as personality, cognition, family background, or interpersonal relationships and it is very unlikely each one of these factors be responsible for depression development by themselves (1).With the onset of adolescence, girls are reported to have depression at a rate two or three times higher than that in boys, with this sex difference remaining throughout their lives (2). Baumeister and Leary (3) believe that developing and continuing persistent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…Emotional loneliness and social loneliness were both associated with feelings of depression and anxiety. These findings were consistent with the results of previous studies on adults and high school students [ 12 , 44 ]. However, the direction of causality is unclear: Cacioppo et al [ 45 ] found a reciprocal association between depression and loneliness, whereas the results of van Winkel et al [ 46 ] and Cacioppo et al [ 47 ] suggested that loneliness led to depression.…”
Section: Discussionsupporting
confidence: 93%
“…Emotional loneliness and social loneliness were both associated with feelings of depression and anxiety. These findings were consistent with the results of previous studies on adults and high school students [ 12 , 44 ]. However, the direction of causality is unclear: Cacioppo et al [ 45 ] found a reciprocal association between depression and loneliness, whereas the results of van Winkel et al [ 46 ] and Cacioppo et al [ 47 ] suggested that loneliness led to depression.…”
Section: Discussionsupporting
confidence: 93%
“…That study was one of the few in which DJGLS was used for the assessment of loneliness [21]. Similar to us, Diehl et al and the authors of a study on a group of girls aged 15-18 years demonstrated a positive correlation between loneliness and degree of anxiety and depression [45].…”
Section: Discussionsupporting
confidence: 55%
“…A study investigating college students in 26 countries in Africa, Asia, the Caribbean, and Latin America has reported similar prevalence rates, with 24.0% noted as moderate and 12.8% as severe [ 7 ]. Depressive symptoms have a negative impact on academic achievement [ 8 ], interpersonal relationships, and the daily life [ 9 ] of college students. Furthermore, depressive symptoms have been reported to increase the risk of suicidal ideation or behavior [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%